LANJUT USIA (LANSIA) DALAM KEBIJAKAN PARIWISATA DI HONG KONG (TIONGKOK): TAHUN 1978-2016 - Erlita Tantri (Jurnal Kajian Wilayah, 2018)
Hong Kong is one of the special administrative regions of China which is very well known as a tourist destination. The increasing number of elderly in someregions ofChinaand the growth of elderly’s interest in tourismhaveencouraged the development of tourism in Hong Kong asthe populartourist destinations for any ages including the elderly. Then, What wasthe tourism policy that had been taken by China, especially the Hong Kong administrationin order to attract tourists from various ages, regions, ethnicities and cultures? What weretourism offers that suppliedby Hong Kongadministrationto tourists including the elderly? Through literature studies and in-depth interviews, this study tries to lookthe tourism policies in China, especially Hong Kong for elderly tourists. China, especially Hong Kongwerevery concerned regarding totourism policiessince the beginning of China's reform or when Hong Kong washeld by the British government. These were related to the role of tourism as one of the money machines for state or regional income. Hong Kong has offereda variety of interesting entertainment for tourists, both young and old. Various offers of tourist entertainment have spoiled visitors, including the elderly. In addition, there are many facilities, tourist infrastructures, and the convenience forgetting any kindsof entertainmentthatintended for elderly tourists. These are that haveled to the increasing number of elderly people to visit Hong Kong tourism.Keywords: elderly, tourism, policy, historyAbstrakHong Kong merupakan salah satu wilayah administrasi khusus Tiongkok yang sangat terkenal sebagai tujuan wisata. Seiring dengan meningkatnya jumlah lansia di sejumlah wilayah di Tiongkok serta berkembangnya minat lansia dalam beriwisata, telah mendorong perkembangan pariwisata di Hong Kong yang menjadi salah satu destinasi wisata favorit bukan hanya bagi kaum muda, anak-anak dan dewasa, namun juga bagi lansia. Lalu, Bagaimana kebijakan pariwisata yang diambil oleh pemerintah Hong Kong dalam rangka menarik wisatawan dari berbagai segmen usia, wilayah, etnis, dan budaya? Bagaimana dengan pariwisata yang ditawarkan Hong Kong kepada wisatawan termasuk lansia? Melalui studi literatur dan wawancara mendalam, studi ini berusaha melihat kebijakan pariwisata di Tiongkok khususnya Hong Kong bagi wisatawan lansia. Tiongkok, khususnya Hong Kong memperlihatkan bahwa pemerintah sangat peduli dengan kebijakan pariwisatanyasejak awal reformasi Tiongkok bahkan sejak di pegang oleh pemerintahan Inggris. Hal ini terkait dengan peran pariwisata sebagai salah satu mesin uang bagi pendapatan negara atau wilayah. Hong Kong sendiri menawarkan beragam hiburan menarik bagi wisatawan, baik muda maupun tua. Berbagai tawaran hiburan wisata telah memanjakan pengunjung termasuk lansia. Selain itu, telah banyak fasilitas, infrastruktur wisata, dan kemudahan untuk mendapatkan jenis hiburan yang ditujukan bagi wisatawan lansia. Hal ini yang mendorong bagi meningkatnya jumlah lansia mengunjungi pariwisata Hong Kong. Kata kunci: lansia, pariwisata, kebijakan, sejarah